2005
DOI: 10.5688/aj690220
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Residents How to Teach: A Scholarship of Teaching and Learning Certificate Program (STLC) for Pharmacy Residents

Abstract: Objectives. In 1999, the University of Kentucky (UK) College of Pharmacy first reported the development of a STLC Program for pharmacy residents. The primary goal of this program was to provide a forum for participants to gain knowledge of contemporary health professions and pharmacy education issues, to develop experience in teaching/learning, and to document accomplishment in this area. Methods. The STLC program was designed as an elective experience that would provide residents with training in various teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
105
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(105 citation statements)
references
References 5 publications
(2 reference statements)
0
105
0
Order By: Relevance
“…A follow-up evaluation of this program was published in 2005. 11 The authors administered a survey to past residents to assess confidence in teaching ability before and after residency training. The survey showed that residents who completed the STLC program had a significantly greater improvement in confidence in teaching ability than residents who did not complete the program.…”
Section: Discussionmentioning
confidence: 99%
“…A follow-up evaluation of this program was published in 2005. 11 The authors administered a survey to past residents to assess confidence in teaching ability before and after residency training. The survey showed that residents who completed the STLC program had a significantly greater improvement in confidence in teaching ability than residents who did not complete the program.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have described efforts to prepare pharmacy students and residents for teaching responsibilities. [1][2][3][4][5][6] Attempts to enhance students' skills and depth of knowledge by offering focused concentrations also have been described in the literature. [7][8][9][10] The Southern Illinois University Edwardsville (SIUE) School of Pharmacy has developed an education concentration for PharmD students to address faculty recruitment and retention.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 Text and video preceptor training resources are available and several programs have been described in the literature. however, few of these programs include preceptor coaching or a structured practical experience (SPE) of significant duration, 4,5 and even fewer have been evaluated using measures other than satisfaction. 4,5 Finally, no programs have been described in which the course itself forms the basis for training preceptor coaches.…”
Section: Resultsmentioning
confidence: 99%